Evidence of Pathogen-Induced Immunogenetic Selection across the Large Geographic Range of a Wild Seabird. (25th February 2020) - Levy, Hila; Fiddaman, Steven R; Vianna, Juliana A; Noll, Daly; Clucas, Gemma V; Sidhu, Jasmine K H; Polito, Michael J; Bost, Charles A; Phillips, Richard A; Crofts, Sarah; Miller, Gary D; Pistorius, Pierre; et al.
Abstract: Over evolutionary time, pathogen challenge shapes the immune phenotype of the host to better respond to an incipient threat. The extent and direction of this selection pressure depend on the local pathogen composition, which is in turn determined by biotic and abiotic features of the environment. However, little is known about adaptation to local pathogen threats in wild animals. The Gentoo penguin ( Pygoscelis papua ) is a species complex that lends itself to the study of immune adaptation because of its circumpolar distribution over a large latitudinal range, with little or no admixture between different clades. In this study, we examine the diversity in a key family of innate immune genes—the Toll-like receptors (TLRs)—across the range of the Gentoo penguin. The three TLRs that we investigated present varying levels of diversity, with TLR4 and TLR5 greatly exceeding the diversity of TLR7 . We present evidence of positive selection in TLR4 and TLR5, which points to pathogen-driven adaptation to the local pathogen milieu. Finally, we demonstrate that two positively selected cosegregating sites in TLR5 are sufficient to alter the responsiveness of the receptor to its bacterial ligand, flagellin. Taken together, these results suggest that Gentoo penguins have experienced distinct pathogen-driven selection pressures in different environments, which may be important given the role of the Gentoo penguin as a sentinel species in some of the world's most rapidly changing environments.